An Analysis on the Role and Values of Dowry: The Motives Behind Traditional Marriage of Sikka Krowe Ethnic - Saputra, Mohamad Zidan Yayan; Naro, Antonius M. K.; Mayaputri, Velmi (Buletin Edukasi Indonesia, 2025)
Dowries often becomes an issue and may all up different perspectives  in various cultures.However, it is important to understand that a dowry should be a symbol of consent and not a tool to create tension or reinforce inequality. This research aims to determine the perspective of University of Muhammadiyah Maumere students regarding the role and value of dowry among Sikka Krowe ethnic group. This research focuses on how the students view the role and value of the dowry in maintaining the social traditions and the religious values . This research employs qualitative research design. To find out overall perceptions, interviews was conducted. The informants were students of University of Muhammadiyah Maumere. The results of this research claimed that students' perspective about the role and value of dowry vary. Most respondents considered dowry to have a significant role in shaping their identity and moral values. However, there are differences in the way they implement dowry values in everyday life. Some students emphasized the importance of maintaining dowry traditions and values in all aspects of life, while others felt that some dowry values were becoming less relevant. The suggestion from this research is that it is necessary to integrate the role and values of dowry into the higher education curriculum to strengthen its understanding and implementation and that higher education must pay special attention to training in interpersonal skills and professional ethics based on dowry values. It is important to prepare students not only in terms of technical knowledge and skills, but also in terms of attitudes and behavior that reflect dowry values in their interactions with society.